Histopathological Analysis of Neoplastic and Non-Neoplastic Lesions of Ovary : A 4 Year Study in Eastern Nepal - Singh, Mrinalini; Jha, KK; Kafle, SU; Rana, R; Gautam, P (Birat Journal of Health Sciences, 2017)
Introduction Ovarian neoplastic and nontineoplastic lesions form a pelvic mass and cause gynaecological problems. Therefore, proper recognization and classification is important for appropriate therapy. Objective To study the morphological patiern and classify the neoplastic and nontineoplastic ovarian lesions in terms of age and size. Methodology A retrospective study conducted at Sriram Diagnostic Clinic, Biratnagar, Nepal and Birat Medical College, Tankisinwari, Morang, Nepal during a period of March 2012 to February 2016. All abdominal hysterectomy specimens with bilateral or unilateral salpingo-oophorectomy and all ovarian surgeries presenting with either solid or cystic ovarian lesions were included in the study for histopathological analysis. Normal appearing ovaries on gross and microscopic examination were excluded from the study. Results A total of 522 cases were studied. Out of which 329 (63%) were non-neoplastic and 193 (37%) were neoplastic. Follicular cysts comprised of 112 (34%) cases, and it was the most common non neoplastic lesion. The age of patients with non-neoplastic lesions and neoplastic lesions varied from 16-54 years and 13-72 years respectively. Size of nonneoplastic and neoplastic lesions varied from 2-12 cm and 2- 19 cm respectively. Among the 193 neoplastic ovarian lesions, 181 (94 %) were benign, as well as 4 (2%) were borderline and 8 (4 %) were malignant. Mature cystic teratoma was the commonest benign tumor followed by Serous cystadenoma. Serous cystadenocarcinoma was the commonest occurring malignant tumor followed by Mucinouscystadenocarcinoma. Conclusion Varying types of both non neoplastic and neoplastic ovarian lesion were seen. Among the non-neoplastic and neoplastic lesion, the most commonly encountered lesion was follicular cyst and mature cystic teratoma respectively. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 168-174